Corporate Responsibility and Sustainable Development: an integrative perspective - Jones, Bryce (New York NY Research Press, 2023)
Corporate responsibility (CR) refers to the effect of an organization on the economy, society, and the environment. Sustainable development is referred to as the development that satisfies the requirements of the current generation without jeopardizing the capacity of future generations to satiate their needs. CR and sustainable development are related concepts, which directly impact corporate governance. Both of these emphasize on making efforts to protect, recycle and regenerate the environment. CR helps businesses in gaining loyalty and trust of their stakeholders by promising to generate profits in a sustainable manner. It aims to integrate environmental, economic and social obligations into business operations. It also aims to establish sustainable business growth and demonstrate a good influence on the consumers, environment, communities, employees, and shareholders. This book presents an integrative perspective on corporate responsibility and sustainable development. It is appropriate for those seeking detailed information in this area of study.
Keywords: Social responsibility of business; Sustainable development; Industries--Environmental aspects